Exploring differences in Statics Concept Inventory scores among students and practitioners. Issue 1 (28th January 2019) - Brown, Shane; Lutz, Ben; Perova‐Mello, Natasha; Ha, Oai
Abstract: Background: Conceptual understanding is critical to both engineering education and practice. In fact, many undergraduate courses focus on developing students' knowledge and understanding of core engineering concepts. At the same time, a growing body of literature points to substantial gaps across educational and professional practice contexts, including how problems are embodied and solved. Purpose: The purpose of this study was to explore potential differences in conceptual understanding across engineering students and professional engineers. To do so, we compared the responses of civil engineering practitioners to the Statics Concept Inventory (SCI) to those of engineering students enrolled in statics courses. Design/Method: We administered the SCI to 95 practicing civil engineers and compared their responses to an existing dataset from 1, 372 engineering students. We conducted three comparisons: overall SCI score, concept subscores, and item‐by‐item. Results: Students generally outperformed engineers on the SCI in terms of overall performance. However, on closer inspection, students' superior performance appears to be driven by differences in knowledge or understanding of specific statics concepts rather than a stronger understanding in general. Conclusions: We caution against interpretations that imply students have a better understanding of statics concepts. Instead, our results suggest that differences in the way concepts are situated and applied across school and workplace contexts might account for the differences in the performance observed. These findings raise critical questions regarding the nature of concepts and the immutability of common academic representations, and point to the need for further qualitative and exploratory work investigating concepts in practice.